Distinct CD4+ T cell signature in ANA-positive young adult patients - Dei Zotti, Flavia; Moriconi, Chiara; Qiu, Annie; Miller, Anabel; Hudson, Krystalyn E. (Frontiers in Immunology, 2022)
Failure of immune tolerance can lead to autoantibody production resulting in autoimmune diseases, a broad spectrum of organ-specific or systemic disorders. Immune tolerance mechanisms regulate autoreactive T and B cells, yet some lymphocytes escape and promote autoantibody production. CD4+ T cell dysregulation, characterized by decreased or impaired regulatory cells (Tregs) and/or accumulation of memory and effector T cells such as TH17, plays a crucial role in the pathogenesis of these diseases. Antinuclear antibody (ANAs) testing is used as a first step for the diagnosis of autoimmune disorders, although most ANA-positive individuals do not have nor will develop an autoimmune disease. Studying the differences of T cell compartment among healthy blood donors, ANA-negative patients and ANA-positive patients, in which loss of tolerance have not led to autoimmunity, may improve our understanding on how tolerance mechanisms fail. Herein, we report that ANA-positive patients exhibit a distinct distribution of T cell subsets: significantly reduced frequencies of recent thymic emigrants (RTE) and naïve T cells, and significantly increased frequencies of central memory T cells, TH2 and TH17 cells; modulations within the T cell compartment are most profound within the 18-40 year age range. Moreover, CD4+ T cells in ANA-positive patients are metabolically active, as determined by a significant increase in mTORC1 and mTORC2 signals, compared to ANA-negative patients and healthy blood donors. No significant impairment of Treg numbers or pro-inflammatory cytokine production was observed. These results identify a unique T cell signature associated with autoantibody production in the absence of autoimmune disease.